Cajal, Retzius, and Cajal–Retzius cells - Martínez-Cerdeño, Verónica; Noctor, Stephen C. (Frontiers in Neuroanatomy, 2014)
The marginal zone (MZ) of the prenatal cerebral cortex plays a crucial role in cellular migration and laminar patterning in the developing neocortex and its equivalent in the adult brain - layer I, participates in cortical circuitry integration within the adult neocortex. The MZ/layer I, which has also been called the plexiform layer and cell-poor zone of Meynert, among others, is home to several cell populations including glia, neurons and Cajal-Retzius (CR) cells. Cajal once said that the MZ is one of the oldest formations in the phylogenetic series, and that the characteristics of layer I in human are similar in all vertebrates except fish (Ramon y Cajal, 1899). Despite the presence of CR cells in the MZ/layer I of all developing and adult vertebrate brains, and more than one hundred years of research, the phenotype and function of layer I cells have still not been clearly defined. Recent technological advances have yielded significant progress in functional and developmental studies, but much remains to be understood about neurons in MZ/layer I. Since the time of Retzius and Cajal, and continuing with modern era research from the likes of Marín-Padilla, the study of CR cells has been based on their morphological characteristics in Golgi staining. However, since Cajal’s initial description, the term ‘CR cell’ has been applied differently and now is often used to indicate reelin (Reln) positive cells in MZ/layer I. Here we review the history of work by Cajal, Retzius and others pertaining to CR cells. We will establish a link between original descriptions of CR cell morphology by Cajal, Retzius and others, and current understandings of the cell populations that reside in MZ/layer I based on the use of cellular markers. We propose to use the term ‘CR cell’ for the class of neurons that express Reln in the MZ/layer I in both prenatal, developing and adult cerebral cortex.